Canal House : cook something : recipes to rely on - Hirsheimer, Christopher; Hamilton, Melissa (Voracious, Little, Brown and Company, 2019)
Canal House's Melissa Hamilton and Christopher Hirsheimer are home cooks writing about home cooking for other home cooks. From a lifetime of making dinner every single night, they've edited their experience down to the essentials: 300 simple and genius recipes that reveal the building blocks of all good cooking, and are guaranteed to make you a better cook. Each chapter of Cook Something helps you master a key ingredient or powerful technique, moving from simple (a perfect soft-boiled egg, and how to make it uncommonly delicious) to ambitious (a towering chocolate souffle). Recipes for salad dressings, sauces, braises, roasts, meatballs, vegetables, and even perfect snacks and sweets help novice and experienced cooks alike reach for the perfect dish for any occasion.